FINANCIAL PERFORMANCE: THE ROLE OF GOOD CORPORATE GOVERNANCE, RISK MANAGEMENT, AND INNOVATION - Putri, Jennie Calista; Khairudin, Khairudin; Aminah, Aminah (Transpublika Publisher, 2024)
The performance of a company can be considered good if its financial reports show an increase in profit. This study aims to examine the relationship between Good Corporate Governance, Risk Management, and Innovation on the Financial Performance of conventional banking companies. The study utilizes a quantitative method, with data sourced from secondary sources. Classical assumption testing, F-test, t-test, and multiple linear regression analysis techniques are employed. The results of this research are as follows: (1) The board of directors has a positive and significant impact on Financial Performance, (2) The Audit Committee has a positive and significant impact on Financial Performance, (3) Independent Board of Commissioners has a positive and significant impact on Financial Performance, (4) Risk Management has a negative and significant impact on Financial Performance, (5) Innovation has a positive and significant impact on Financial Performance. The Board of Directors, Audit Committee, Independent Board of Commissioners, NPL, and Mobile Banking simultaneously influence Financial Performance in conventional banks listed on the Indonesia Stock Exchange for the period 2021-2022.